2021
DOI: 10.1051/shsconf/20219202064
|View full text |Cite
|
Sign up to set email alerts
|

Beneish M-score: A measure of fraudulent financial transactions in global environment?

Abstract: Research background: Earnings is a source of information for capital owners, potential investors, competitors, customer and supplier of the company. Managers have the direct motivation and knowledge and use adequate techniques to adjust legally the reported earnings to meet the specific requirements of the company and achieve stable financial results. Thus, earnings management is currently the most provocative and highly topical issue in the field of finance and accounting at the global perspective. Purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…According to Valaskova and Fedorko (2021), the Beneish model utilises several financial ratios of a given business entity to determine the probability that reported earnings had been manipulated.…”
Section: Methodsmentioning
confidence: 99%
“…According to Valaskova and Fedorko (2021), the Beneish model utilises several financial ratios of a given business entity to determine the probability that reported earnings had been manipulated.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, integrated reporting can prevent short-term oriented corporate behavior and promote long-term value creation that is attractive to stakeholders. According to Valaskova & Fedorko (2021), detecting specific income manipulations in the economic sector must have global financial reporting principles and disclose a certain level of Manipulation in companies in selected countries in the Visegrad grouping. Detecting profits using the M-score measurement will help protect business partners in detecting fraudulent behavior, especially globally…”
Section: Severalmentioning
confidence: 99%
“…This study is interesting to study because earnings management practices use the Beneish M-score where this model is for several views (Ayu et al, 2020;Siekelova et al, 2020;Svabova et al, 2020) in detecting Manipulation of financial statements will provide benefits for the parties who are in positions of authority which provide increased return expectations as well as prevention of damage to the company's reputation for analysts. According to Valaskova & Fedorko (2021), the use of the beneficial M-score model revealed that 71% in cases of financial reporting was the most significant. Franceschetti & Koschtial's (2013) study adopting the Beneish Mscore is considered an appropriate model system for detecting Manipulation in corporate earnings management.…”
Section: Beneish Modelmentioning
confidence: 99%
“…Hołda (2020) showed the efficacy of eight ratios M-score over five ratio M-score for finding the manipulating firms of Warshow stock exchange. In 2021, Valaskova and Fedorko (2021) showed that the Beneish model can predict the fraudulent behavior of companies by detecting the manipulating one. Shakouri, Taherabadi, Ghanbari, and Jamshidinavid (2021) did a regression analysis and found that DSRI, GMI, AQI, SGI, DEPI and TATA of the Beneish model significantly impacted fraudulent financial reporting.…”
Section: Literature Reviewmentioning
confidence: 99%